Teaching English as a second or foreign language - Celce-Murcia, Marianne (Boston, MA : Heinle & Heinle/Thomson Learning, 2001)
Offers a theoretical background and practical applications designed to help teachers of English as a second language decide which methods, materials, and resources can and should be used in their classrooms.
Includes bibliographical references (p. 553-574) and index.
Professional
Keywords: English language -- Study and teaching -- Foreign speakers; English as a second language